Energy for Sustainable Future - Mahlia, T M Indra; Fattah, Islam Md Rizwanul (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Energy and the environment are irrevocably interrelated, and they are critical factors that influence the development of societies. The pollution of the environment without considering various consequences has become one of the most important global issues today. This environmental pollution is mainly the result of increases in economic activities, population, transportation, electricity generation, agriculture, forestry, and land use. The exigency of energy for these activities, the rapidly rising price of petroleum oil, the harmful effect of greenhouse gases, and the quest for energy security have steered our attention towards sustainable sources of energy. It is fundamental to find innovative solutions that are sustainable from the perspective of energy management and environmental protection. This book includes three review articles which review the state-of-the-art of different sustainable energy resources. These articles include ammonia as a renewable energy carrier, integration of solar photovoltaic, and bio-oil from waste tires for automotive engine application. In addition, eight research studies reveal new knowledge about energy for a sustainable future. The topics covered span many diverse areas associated with sustainable energy, including various biofuels, photovoltaic, and other aspects of sustainability. These complementary contributions provide a substantial body of knowledge in the field of Renewable and Sustainable Energy.